Analysis Behavior Intention in Using Business-to-Business E-Commerce Case Study in MSMEs - Levyda, Levyda; Jumini, Jumini; Sri Mulatsih, Listiana (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2024)
An integral part of the Indonesian economy is e-commerce. However, there are still many MSMEs who prefer offline trading. This study analyzes business-to-business e-commerce through the lens of the Technology Acceptance Model. This research aim to examine the influence of perceived usefulness and perceived ease of use on behavior intention and actual usage of business-to-business e-commerce, as well as the influence of behavior intention and actual usage. The respondents of this research were business-to-business platform users, totaling 57 MSMEs in Jakarta and surrounding areas. The data was processed with partial least squares (PLS) and using Bootstrap 500. The research results showed the influence of perceived usefulness and perceived ease of use on behavior intention and actual usage; perceived ease of use affected perceived usefulness, and behavior intention had no effect on actual use of business-to-business e-commerce. Perceived usefulness has a stronger role than perceived ease of use in actual usage, but perceived ease of use has a bigger role than perceived usefulness in influencing behavioral intention. Platform management must improve the platform's user benefits in order to boost e-commerce usage.